Imaging methane hydrates growth dynamics in porous media using synchrotron X‐ray computed microtomography. (10th December 2014) - Kerkar, Prasad B.; Horvat, Kristine; Jones, Keith W.; Mahajan, Devinder
Abstract Commercial‐scale methane (CH4) extraction from natural hydrate deposits remains a challenge due to, among other factors, a poor understanding of hydrate‐host sediment interactions under low‐temperature and high‐pressure conditions that are conducive to their existence. We report the use of synchrotron X‐ray computed microtomography (CMT) to image, for the first time, time‐resolved pore‐scale methane CH4 hydrate growth from an aqueous solution containing 5 wt % barium chloride (BaCl2) and pressurized CH4 hosted in glass beads, all contained in an aluminum cell with an effective volume of 3.5 mL. Multiple two‐dimensional (2‐D) cross‐sectional images show CH4 hydrates, with 7.5 µm resolution, distributed in patches throughout the system without dependence on distance from the cell walls. The time‐resolved three‐dimensional (3‐D) images, constructed from the 2‐D slices, exhibited pore‐filling hydrate formation from dissolved CH4 gas, similar to natural CH4 hydrates (sI) in the marine environment. Furthermore, the 3‐D images show that the aqueous phase was the wetting phase of the glass beads, i.e., the host and the formed hydrate were separated by an aqueous layer. These results provide some fundamental understanding of the nucleation phenomenon of gas hydrate formation at the pore scale. Pore‐filling CH4 hydrate growth is likely to result in a reduced bulk modulus, and thus, could affect seafloor stability during the reverse phenomenon, i.e., dissociation of natural hydrate deposits.